Effects of Perceptual Motor Exercise on Dexterity in Children with Down Syndrome: A Single Subject Study - Narges Ghamari; Shahla Rafeei; Ramezan Soltani; Zahra Ghamari; Mina Ahmadi Kahjoogh (Vesnu Publications, 2016)
Introduction: Down syndrome, as a genetic disorder, is one of the major causes of mental retardation and results in delayed motor skills such as fine motor, gross motor, and visual motor control and power. Dexterity is a functional hand skill that requires coordination between gross and fine motor functions that are affected by motor problems in these children. Considering the importance of the development of gross and fine motor functions, and coordination between them to perform activities such as dexterity, the purpose of this study was to investigate the effects of perceptual motor exercise on dexterity in children with Down syndrome. Materials and Methods: The present study was a clinical trial with a single-subject design. The study subjects were selected through convenience sampling. In the basic phase, participants were evaluated twice a week using the Purdue Pegboard Test. In the treatment phase, the subjects participated in perceptual motor exercise sessions 3 times a week for 60 minutes for a period of 1.5 months. To investigate the variation pattern in the basic and treatment phases, C-statistics and Bayesian analysis were used. Results: Bayesian analysis showed that the effect of perceptual motor exercise on dexterity, based on mean montage score, was strong in 2 participants, strong to very strong in 1 participant, moderate to strong in 1 participant, and weak in 1 participant. Conclusion: The results indicate that perceptual motor exercise can be an effective intervention for improving dexterity in children with Down syndrome. Thus, studies with stronger methodology are required